Modified one-phase-low-pH method for bacteria or enzyme-induced carbonate precipitation for soil improvement - Cui, Ming-Juan (2022)
One of the latest developments in biocementation is the use of one-phase-low-pH MICP or EICP method as a more effective and efficient alternative to the traditional two-phase method for the treatment of sandy soil. However, the one-phase-low-pH method has its own limitation. The pH of the solution has to be adjusted before every treatment. In this study, a modified one-phase-low-pH MICP or EICP method is proposed in order to simplify the treatment procedure to improve the efficiency of biotreatment in real constructions. In this method, the low-pH bacteria or urease solution is only used together with the cementation solution (i.e., CaCl2 and urea) for the first treatment and for the subsequent treatment, only cementation solution is used. The test results show that using the modified one-phase-low-pH MICP method with a bacterial solution of a volume ratio of 0.75 is comparable to that using the original one-phase-low-pH method, and 80% of the calcium conversion efficiency can be maintained for up to 5 treatments. However, the modified one-phase-low-pH EICP method may only be used for the first 2 or 3 treatments due to the relatively poor durability of urease enzyme in inducing calcium carbonate during the subsequent injections of cementation solution.